PERBEDAAN HASIL BELAJAR SISWA ANTARA PEMBERIAN TES FORMATIF DENGAN NILAI TUGAS - Evi Ermawati, (Pendidikan Ekonomi, 2011)
The aim of the study is investigate whether there is a difference in the assignment score and formative test score. The population was all the tenth year students of Accounting classes at SMK Negeri I Mojoagung in the academic year 2008-2009, while the sample was the tenth year students of Accounting class I.  The data were collected through interview, documentation, and tests. The data were then analyzed with t-test. The result indicates that there is a significant difference   in the students assignment score and formative test score.